Thrombin-Antithrombin III Complexes in the Prediction of Deep Vein Thrombosis Following Total Hip Replacement - Hoek, J A; Nurmohamed, M T; ten Cate, J W; Büller, H R; Knipscheer, H C; Hamelynck, K J; Marti, R K; Sturk, A (Thrombosis and Haemostasis, 1989)
In 196 consecutive patients who underwent elective total hip surgery we investigated the diagnostic accuracy of the thrombinantithrombin III complex immunoassay, as assessed on the first, fourth and tenth postoperative day, for the development of deep vein thrombosis (DVT). Patients received either LMWheparinoid (n = 97) or placebo (n = 99) and underwent contrast venography on the tenth postoperative day.Thrombin-antithrombin III (T-AT) plasma levels were raised in all patients on the first postoperative day and gradually decreased during the study period. T-AT plasma levels were significantly higher in patients developing DVT when compared to patients without DVT and remained so until day 10. This difference was apparent both in the LMW-heparinoid group as well as in the placebo-treated patients.ROC-curve analysis revealed no satisfactory discriminative power for the diagnosis of developing DVT at any of the studied cut-off values for T-AT.We conclude that the postoperative determination of T-AT complex plasma concentrations in hip surgery patients has no clinical utility in the prediction of postoperative DVT.
Keywords: Thrombin-antithrombin III complexes; Deep vein thrombosis; Total hip replacement surgery; Low molecular weight heparinoid